Antiferromagnet-ferromagnet phase transition in lightly doped manganites - Troyanchuk, I.O.; Khomchenko, V.A.; Eremenko, V.V.; Sirenko, V.A.; Szymczak, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
Magnetic and structural phase diagrams of the La0.88MnOx, La1–xSrx(Mn1–x/2Nbx/2)O3, Nd1–xCaxMnO3, and Bi1–xCaxMnO3 series constructed on the basis of x-ray, neutron powder diffraction, Young’s modulus, magnetization and resistivity measurements are presented. It is shown that the main factor controlling the antiferromagnet–ferromagnet phase transition in the manganites is a type of an orbital state. The results are discussed in the framework of structurally driven magnetic phase separation model.